Two novel serine proteases from Scylla paramamosain involved in the synthesis of anti-lipopolysaccharide factors and activation of prophenoloxidase system. Issue 84 (January 2019) - Wei, Zibo; Sun, Wanwei; Tran, Ngoc Tuan; Gong, Yi; Ma, Hongyu; Zheng, Huaiping; Zhang, Yueling; Li, Shengkang
Abstract: Serine proteases (SPs) are important in various immune responses, including prophenoloxidase (proPO) activation, antimicrobial peptides (AMPs) synthesis, and hemolymph coagulation in invertebrates. In this study, SP3 and SP5 of mud crab ( Scylla paramamosain ) were studied. SP3 and SP5 were expressed in all examined tissues (mainly in hemocytes), and are associated with the immune responses of mud crab to Vibrio parahemolyticus and Staphylococcus aureus, as well as interacted with TRAF6, and are involved in the activation of anti-lipopolysaccharide factors (ALFs) probably through the TLR/NF-κB pathway. Depletion of SP3 inhibited the expression of ALF1, ALF2, ALF3, and ALF6, while knockdown of SP5 significantly decreased ALF5, and ALF6. Furthermore, both SP5 and TRAF6 regulated the PO activity in the hemolymph of mud crab. Overexpression assay showed that both SP3 and SP5 could enhance the promoter activities of ALFs in mud crab. Taken together, the results of this study indicate that SP3 and SP5 might play important roles in the immune system of mud crab against pathogen invasion. Highlights: Full-length of SP3 with 1366 bp, and SP5 with 1655bp were isolated from mud crab. SP3 and SP5 interacted with TRAF6 and were associated with the activation of ALFs. Both SP5 and TRAF6 regulate PO activity in the hemolymph of mud crab.